Responsible Citizens : Individuals, Health, and Policy Under Neoliberalism - Brown, B. J. (Brian J.) (Key issues in modern sociology., 2012)
'Responsible Citizens' reveals how rising emphasis on the individual has gone hand in hand with an increase in subtle authoritarianism - particularly within public services - such that a kind of 'governance through responsibility' is today being enforced upon the population.